2016
DOI: 10.1302/2046-3758.56.bjr-2015-0014.r1
|View full text |Cite
|
Sign up to set email alerts
|

Circulating exosome levels in the diagnosis of steroid-induced osteonecrosis of the femoral head

Abstract: ObjectivesCirculating exosomes represent novel biomarkers for multiple diseases. In this study, we investigated whether circulating exosome levels could be used as a diagnostic biomarker for steroid-induced osteonecrosis of the femoral head (ONFH).MethodsWe assessed the serum exosome level of 85 patients with steroid-induced ONFH and 115 healthy donors by Nanosight detection. We then assessed the diagnostic accuracy of serum exosomes by receiver operating characteristic curve analysis.ResultsThe circulating ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…As a common disease, osteonecrosis is attracting more and more attention. In order to improve the early diagnosis of GC-induced ONFH or guide clinical trials in GC-induced osteonecrosis, studies of circulating exosomes 24 and microvesicles 25 have aroused widespread interest. Within the past decade, extracellular vehicles (EVs) have emerged as key mediators involved in signal transduction between cells to regulate a diverse range of biological processes in both prokaryotes and eukaryotes 26 .…”
Section: Introductionmentioning
confidence: 99%
“…As a common disease, osteonecrosis is attracting more and more attention. In order to improve the early diagnosis of GC-induced ONFH or guide clinical trials in GC-induced osteonecrosis, studies of circulating exosomes 24 and microvesicles 25 have aroused widespread interest. Within the past decade, extracellular vehicles (EVs) have emerged as key mediators involved in signal transduction between cells to regulate a diverse range of biological processes in both prokaryotes and eukaryotes 26 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the cost of MRI scanning is high causing a heavy burden on healthcare system [ [24] , [25] , [26] ], highlighting the need for a convenient laboratory test to detect ONFH development. To our knowledge, urinary miR-150 showed the highest diagnostic power among all known biomarkers for idiopathic ONFH [ 10 , [39] , [40] , [41] , [42] , [43] , [44] ].…”
Section: Discussionmentioning
confidence: 99%
“…Primarily, our results showed that traumatic ONFH-Exo could promote cell proliferation, and the rats treated with traumatic ONFH-Exo exhibited increased number of branch points, length of total tube, area of cell migration, and number of invasive cells. Exosomes are a kind of cellsecreted vesicle that are predominantly found in urine, blood, cultured medium, and various biologic fluids, and they serve as promising biomarkers in the diagnosis and treatment of a number of diseases, including pancreatic cancer, chronic kidney disease, and acute coronary syndrome (31). An exosome is internalized upon change of its motion mode to a rapid directed mode (32).…”
Section: Discussionmentioning
confidence: 99%